Analysis of the Effects of Risk Management and Knowledge Sharing on Supervisory Effectiveness - Adrie Oktavio; Verina Wijaya; Moses Soediro; Agustinus Nugroho; Rizki Adityaji; Erris Kusumawidjaya (Indonesian Journal Economic Review (IJER), 2026)
This study examines the effect of risk management and knowledge sharing on supervisory effectiveness at PT Ungaran Sari Garment III, Pringapus 7 Unit. A quantitative approach was applied using data collected from 100 employees selected through a structured sampling technique. The data were analyzed using multiple linear regression with a significance level of 5 percent. The findings show that risk management has a positive and significant effect on supervisory effectiveness, indicating that well-implemented risk identification, assessment, and control procedures support more effective supervision. Knowledge sharing also demonstrates a positive and significant influence, suggesting that the exchange of experience, skills, and work-related information among employees contributes to better coordination and monitoring processes. Simultaneously, both variables strengthen supervisory effectiveness, as reflected in the coefficient of determination (R²) of 51.9 percent, while the remaining variance is explained by other factors not examined in this study. These results are consistent with enterprise risk management and knowledge management perspectives, which emphasize alignment between organizational systems and employee interaction in achieving effective supervision.